Dark corners eaudiobook - Goldin, Megan (Macmillan Audio, 2023)
This program features multicast narration. "Samantha Desz and January LaVoy take this novel to new heights by giving a realistic voice to every emotion and scene. Brava!"- The Reading Frenzy "Narrators ... Samantha Desz and January LaVoy are ... perfect [in] Megan Goldin's latest thriller involving a true-crime podcaster and her coverage of a rape trial in a North Carolina town. Desz and LaVoy ensure that Rachel Krall and her podcast unfold in an authentic manner that depicts her as powerful and tenacious." — AudioFile on The Night Swim "A gripping story that is equal parts shocking, unnerving, and thrilling. Goldin takes the 'true crime' trope to new and unexpected territory." —Karin Slaughter, New York Times and #1 international bestselling author of Girl, Forgotten Rachel Krall, the true crime podcaster star of Megan Goldin's acclaimed The Night Swim, returns to search for a popular influencer who disappears after visiting a suspected serial killer. Terence Bailey is about to be released from prison for breaking and entering, though investigators have long suspected him in the murders of six women. As his release date approaches, Bailey gets a surprise visit from Maddison Logan, a hot, young influencer with a huge social media following. Hours later, Maddison disappears, and police suspect she's been kidnapped—or worse. Is Maddison's disappearance connected to her visit to Bailey? And why was she visiting him in the first place? When they hit a wall in the investigation, the FBI reluctantly asks for Rachel Krall's help in finding the missing influencer. Maddison seems to only exist on social media; she has no family, no friends, and other than in her posts, most people have never seen her. Who is she, really? Using a fake Instagram account, Rachel goes undercover to BuzzCon, a popular influencer conference, where she discovers a world of fierce rivalry that may have turned lethal. When police find the body of a woman with a tattoo of a snake eating its tail—identical to a tattoo Rachel had seen on Bailey's hand—the FBI must consider a chilling possibility: Bailey has an accomplice on the outside and a dangerous obsession with influencers, including Rachel Krall herself. Suddenly the target of a monster hiding in plain sight, Rachel is forced to confront the very real dangers that lurk in the dark corners of the internet. A Macmillan Audio production from St. Martin's Press.